2014
DOI: 10.5573/jsts.2014.14.3.300
|View full text |Cite
|
Sign up to set email alerts
|

Load-Balance-Independent High Efficiency Single-Inductor Multiple-Output (SIMO) DC-DC Converters

Abstract: Abstract-A single-inductor multiple-output (SIMO) DC-DC converter providing buck and boost outputs with a new switching sequence is presented. In the proposed switching sequence, which does not require any additional blocks, input energy is delivered to outputs continuously by flowing current through the inductor, which leads to high conversion efficiency regardless of the balance between the buck and boost output loads. Furthermore, instead of multiple output loop compensation, only the freewheeling current f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Due to advancement of circuit technology, the research area of the single-output concept has become saturated; however, several pieces of research have been completed in the area of analog-controller SIMO DC-DC converters as well. Also, system stability, poor cross regulation and flexibility are the main issues of SIMO converters to achieve excellent performance [2][3][4][5][6]. Studies of the digital-controller converters can be found in [7,8], while the field-programmable gate array (FPGA), microcontrollers, and compact reconfigurable input output (cRIO) play key roles in the operation of the corresponding digital controller.…”
Section: Introductionmentioning
confidence: 99%
“…Due to advancement of circuit technology, the research area of the single-output concept has become saturated; however, several pieces of research have been completed in the area of analog-controller SIMO DC-DC converters as well. Also, system stability, poor cross regulation and flexibility are the main issues of SIMO converters to achieve excellent performance [2][3][4][5][6]. Studies of the digital-controller converters can be found in [7,8], while the field-programmable gate array (FPGA), microcontrollers, and compact reconfigurable input output (cRIO) play key roles in the operation of the corresponding digital controller.…”
Section: Introductionmentioning
confidence: 99%